Peran Aktivis Mahasiswa dalam Dinamika Politik di Indonesia - Anggun Rahmatika; Luvi Nur Halimah; Nanda Shinta Pratiwi; Rizqi Khairunnisa; Windu Aprilia; Khoiriyah Ulfah (Jurnal Ilmu Sosial dan Humaniora, 2026)
Student activists play an important role in Indonesia’s democratic system as agents of change and social control. This study examines the role of student activists in Indonesia’s political dynamics through the perspective of political efficacy theory proposed by Stephen C. Craig, Richard G. Niemi, and Glenn E. Silver, which consists of internal political efficacy and external political efficacy. The research aims to understand how student organizations influence students’ political confidence, political participation, and social awareness in contemporary Indonesian politics. This study used a qualitative descriptive method with a purposive sampling technique. The subjects were university students actively involved in student organizations such as BEM, PMII, and other campus organizations. Data were collected through semi-structured interviews, observations, and documentation, then analyzed using the Miles and Huberman interactive model consisting of data reduction, data presentation, and conclusion drawing. The findings show that student organizations significantly improve students’ self-confidence, public speaking skills, political understanding, communication abilities, and social awareness. Student activists also believe that student movements and organizational activities remain effective in conveying aspirations and influencing campus and public policies. However, student activists currently face challenges such as political pragmatism, social media polarization, misinformation, and external political interests that may affect the independence of student movements. In conclusion, student organizations contribute greatly to strengthening political efficacy, political participation, and democratic values among students in Indonesia.